DYNAMICS OF GENDER RESEARCH IN MARKETING: PARADIGMS, PERSPECTIVES, AND VALUE-BASED COMMITMENTS EXAMINED - Paramarta, Vip; Kosasih; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2024)
Research on the dynamics of gender research in marketing explores the evolution of value-based paradigms, perspectives, and commitments that influence our understanding of the role of gender in consumer behavior and marketing strategy. From the simplistic separation of men and women in consumer preferences in the 1970s to the recognition of the complexity of gender identity and the importance of inclusivity, fairness, and sustainability in marketing practices today, these developments reflect changes in social norms, consumer demands, and values. the value of the company. However, this research is faced with challenges, including research methodology that is not always sensitive to gender diversity, difficulties in accurate gender measurement, and the integration of gender frameworks with existing marketing frameworks. To overcome these challenges and deepen our understanding of gender in marketing, an inclusive, collaborative and interdisciplinary approach is needed. More in-depth research on gender in marketing will help develop marketing strategies that are more effective, inclusive and have a positive impact on society as a whole. Therefore, it is recommended to continue to encourage cross-disciplinary collaboration between marketing and gender researchers, and to develop research methods that are more flexible and sensitive to gender diversity. In this way, we can better respond to the complexities of gender in the marketing context and ensure that implemented marketing practices reflect the values of inclusivity, fairness and sustainability.